Ovarian Stimulation Protocols - Allahbadia, Gautam N.; Morimoto, Yoshiharu (Springer India : Imprint: Springer, 2016)
Ovarian Stimulation Protocols is a concise handbook that aims to deliver everything the reader needs to know for performing a risk-free ovarian stimulation for assisted reproductive technique (ART) and get a favorable outcome. Review of crucial issues such as the significance of monitoring ovarian stimulation, advantages and disadvantages of ovarian hyperstimulation versus minimal stimulation, and the use of various drug regimens and stimulation protocols for various patient sub-sets, will help clinicians in selecting the better or more appropriate protocols. The contributors of this book have leading scientific and clinical backgrounds, with years of experience to support their views. The book serves as a handy practical guide, targeting and settling clinical dilemma that ART practitioners commonly experience in their clinics, while providing a window to the newer developments. .